Analyzing area-based rating assessment implementation in Bauchi Metropolis, Nigeria, testing SWOT variables - Baba, Habu Mallam; Kasim, Rozilah; Alhaji Usman, Muktar; Ali Abdu, Abdullahi; Auwal, Umar; Adam Muhammad, AbdulAzeez (Science Arena Publications, 2018)
The Area-based Rating Assessment (AbRA) entails assessing the real property for rating purposes on the basis of the land area only. This study analyzed the implementation of AbRA in Bauchi metropolis, experimentally by testing the helpful factors under both internal and external variables; and subsequently, by testing the harmful factors under the internal and external variables all derived from SWOT analysis, and measuring their effects on the endogenous variable (AbRA). The study derived major themes from SWOT analyses, whose variables under each theme were used as measurement items or sub-themes for the primary data collection. Structural Equation Modelling was used to analyze the impact of the variables on the implementation of AbRA in the study area. It was found that the area assessment required the limited data to conduct the rating assessment, and did not necessarily require periodic revaluation to update the valuation list with the volatilities in value, thus, making AbRA to demand less cost of administration. It was also found that, information on land area can be collected remotely without entry into the individual properties, the process did not defy the residents’ privacy, also, the remote data collection could be done using tools like Google Earth/Map which allowed the ease of reconnaissance and faster inspections and measurements, hence, this study recommended the area-based rating assessment (AbRA) for Bauchi metropolis of Nigeria.